Proteomic evaluation of pathways associated with phosphine-induced mitochondrial dysfunction and resistance mechanisms in Tribolium castaneum against phosphine fumigation: Whole and partial proteome identification - Donghyeon Kim; Sung-Eun Lee (Ecotoxicology and Environmental Safety)
Phosphine (PH3) fumigation is widely used to control insect pests in stored products globally. However, intensive PH3 use has led to the emergence of significant resistance in target insects. To address this issue, this study investigated PH3 resistance mechanisms by conducting both qualitative and quantitative proteomic analyses on the whole proteome of a PH3-resistant Tribolium castaneum strain (AUS-07) using LC-MS/MS. Besides, proteins from both strains were separated in 1D-PAGE, and qualitatively analyzed using LC-MS/MS after in-gel digestion. Differentially expressed proteins (DEPs) with cut-off values (4-fold expression difference and p < 0.05) were selected, and 107 proteins were identified in the AUS-07 strain. Among them, several proteins involved in oxidative phosphorylation were notably upregulated in response to PH3 exposure. Upregulation of Complex I and III in the electron transport chain of the AUS-07 strain may lead to the excessive generation of reactive oxygen species (ROS) in the form of superoxide, which can damage Fe-S cluster-containing proteins such as cytochrome P450s (CYP450s). Upregulation of detoxifying enzymes, such as CYP450s and glutathione S-transferases (GSTs), was observed, likely to repair superoxide-induced damage on CYP450s as well as quenching superoxide. Upregulation of aldose reductases involved in polyol pathways and downregulation of the trehalose transporter were observed, suggesting that PH3-resistance may be linked to diapause-like physiological adaptations, including quiescence. Further studies are essential to quantify polyol levels in the AUS-07 strain and to conduct other molecular analyses to validate the roles of identified DEPs in PH3 resistance. Altogether, our findings suggest a new control strategy to stored product insect pests by other type of fumigant such as ethyl formate with different molecular structure.